Characteristic of HPV Integration in the Genome and Transcriptome of Cervical Cancer Tissues. (19th June 2018) - Li, Weiyang; Qi, Yanwei; Cui, Xiaofang; Huo, Qing; Zhu, Liangxi; Zhang, Aiping; Tan, Meihua; Hong, Qilan; Yang, Yan; Zhang, Huali; Liu, Chuanxin; Kong, Qingsheng; et al.
Abstract : High-risk HPV is clearly associated with cervical cancer. HPV integration has been confirmed to promote carcinogenesis in the previous studies. In our study, a total of 285 DNA breakpoints and 287 RNA breakpoints were collected. We analyzed the characteristic of HPV integration in the DNA and RNA samples. The results revealed that the patterns of HPV integration in RNA and DNA samples differ significantly. FHIT, KLF5, and LINC00392 were the hotspot genes integrated by HPV in the DNA samples. RAD51B, CASC8, CASC21, ERBB2, TP63, TEX41, RAP2B, and MYC were the hotspot genes integrated by HPV in RNA samples. Breakpoints of DNA samples were significantly prone to the region of INTRON (P < 0.01, Chi-squared test), whereas in the RNA samples, the breakpoints were prone to EXON. Pathway analysis had revealed that the breakpoints of RNA samples were enriched in the pathways of transcriptional misregulation in cancer, cancer pathway, and pathway of adherens junction. Breakpoints of DNA samples were enriched in the pathway of cholinergic synapse. In summary, our data helped to gain insights into the HPV integration sites in DNA and RNA samples of cervical cancer. It had provided theoretical basis for understanding the mechanism of tumorigenesis from the perspective of HPV integration in the HPV-associated cervical cancers.